2017
DOI: 10.1002/2017tc004561
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the Distal Piedmont‐Ligurian Rifted Margin in NW Italy: Hints for a Flip of the Rift System Polarity

Abstract: The Alpine Tethys rifted margins were generated by a Mesozoic polyphase magma‐poor rifting leading to the opening of the Piedmont‐Ligurian “Ocean.” This latter developed through different phases of rifting that terminated with the exhumation of subcontinental mantle along an extensional detachment system. At the onset of simple shear detachment faulting, two margin types were generated: an upper and a lower plate corresponding to the hanging wall and footwall of the final detachment system, respectively. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 44 publications
5
37
0
1
Order By: Relevance
“…Studies of the Iberian margin suggest that basinward migration of the sedimentation in more and more distal half‐grabens is a possible mechanism for the tectonic evolution of hyperextended margins (Ranéro & Pérez‐Gussinyé, ). Similarly, interpretations from analog Tethyan margins also indicate this diachronous evolution as proposed initially by Masini et al () and Decarlis et al ().…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Studies of the Iberian margin suggest that basinward migration of the sedimentation in more and more distal half‐grabens is a possible mechanism for the tectonic evolution of hyperextended margins (Ranéro & Pérez‐Gussinyé, ). Similarly, interpretations from analog Tethyan margins also indicate this diachronous evolution as proposed initially by Masini et al () and Decarlis et al ().…”
Section: Discussionsupporting
confidence: 73%
“…While the exhumed domain is relatively symmetric, although ill-defined, the coupled area is wider in the Espirito Santo basin. (5) Regarding kinematic constraints, the interpreted exhumation domains across both margins are contemporaneous with the salt deposition, therefore, indicating that in the scenario presented here, exhumation had to occur between 116 and 111 Ma, which is the age of the salt (Davison, 2007;Dias et al, 1994). However, recent studies put some doubt on the age and onset of salt deposition within the South Atlantic (e.g., Tedeschi et al, 2017), suggesting the evaporites were deposited earlier during the early Aptian Oceanic Anoxic Event 1a interval.…”
Section: Comparison Of the Kwanza And Espirito-santos Profile Interprmentioning
confidence: 65%
“…However, continental crustal thinning is well imaged. Considering these aspects, we rather favour rifting scenario (1) which is also supported by the conceptual model described by Decarlis et al (2017) for the evolution of magma-poor rifted margins. The model includes three phases of extension: (1) An initial stretching phase forming widely distributed half-grabens in the upper crust.…”
Section: Opening Of the Ligurian Basinsupporting
confidence: 60%
“…(a) Paleogeographic reconstruction of the Alpine Tethys during Late Jurassic (see Decarlis et al, ). (b) Simplified cross section across the Alpine Tethys illustrating the main Alpine paleogeographic structural domains and rifting domains (from Decarlis et al, ) (detachment faults in green).…”
Section: Geological Settingmentioning
confidence: 99%
“…During the final phase of hyperextension and exhumation, distal margins can be subdivided in upper plate (hanging wall of the exhumation system) and lower plate (Haupert et al, ; Decarlis et al, ; Figure ). Stratigraphic and structural data reported by Lemoine et al (), Decarlis et al (), and Haupert et al () showed that in the present‐day Alps, the Provençal, Dauphinois, and Upper Austroalpine units (Figure ) represent remnants of the former proximal margins, whereas the internal European units and Lower Austroalpine units are derived from the former distal margin.…”
Section: Geological Settingmentioning
confidence: 99%